Designing and Building Client-Server Based Student Admission Applications - Arip Solehudin; Nono Heryana; Yana Cahyana (Information System; Universitas Buana Perjuangan Karawang, 2020)
Admission of New Students is a routine activity organized by the Educational Institution. Early Childhood Education (PAUD) is included in out-of-school education in the age range of two to five years, the goal is to help improve physical and spiritual growth and development so that children have the readiness to enter further education. Admission of New Students to Al-Qudwah is still done using prospective students visiting Al-Qudwah and filling out the registration form with paper. New Student Admission Application at Al Quwah aims to promote the school to the community at large and can also be registered without parents of prospective students visiting educational institutions. This application makes it easy for parents of prospective students to find out the facilities and infrastructure and the information available on Al Quwah. We built this application using HTML and PHP programming languages with the PHP MySQL database and using the waterfall method.